PELATIHAN PEMBUATAN PROPOSAL PENELITIAN TINDAKAN KELAS DI PONDOK PESANTREN MANBA’UL HIDAYAH BATAM - Ambalegin Ambalegin; Sunargo Sunargo; Nurma Dhona Handayani (MITRA: Jurnal Pemberdayaan Masyarakat, 2023)
Class action research is one of the requirements to promote the teachers’ grades. Teachers are hoped to be able to conduct class action research and solve the teaching learning problem in the classroom. This activity was to assist the teachers of Pondok Pesantren Manba’ul Hidayah Batam to design and write class action research proposals. It was held from January to June 2022 with 17 teachers as the participants by applying the Service-Learning method with the model of lecture, discussion, and practice doing. In each meeting, the training discussed different materials such as lecturing an overview of classroom action research, classroom action research models, teaching-learning process problems in the classroom, teaching methods for problem-solving, and introduction to Turnitin and Mendeley applications. The result of this activity was the improvement in writing the proposal of class action research. It was hoped that the teachers might conduct this type of research to improve the students’ learning quality. The next activity is for the participants to write journal articles to be published.